2008
DOI: 10.1002/glia.20645
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl endopeptidase is revealed following SILAC analysis to be a novel mediator of human microglial and THP‐1 cell neurotoxicity

Abstract: Reactive microglial cells may exacerbate the pathology in some neurodegenerative disorders. Supernatants of stimulated human microglial cells, or their surrogate THP-1 cells, are lethal to cultured human neuroblastoma SH-SY5Y cells. To explore this neurotoxicity, we examined the spectrum of proteins generated by THP-1 cells using the technique of stable isotope labeling by amino acids in cell culture (SILAC). Unstimulated cells were grown in medium with light L-[(12)C(6)] arginine while cells stimulated by lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 52 publications
4
22
0
Order By: Relevance
“…The enzymes may also release pro-inflammatory cytokines and participate in regulating the expression of the cell death signalling molecule FasL [70]. Several MMPs including MMP-2, 3 and 9 contribute to microglial toxicity [68]. In MS brain tissues MMP-2, -7, -9, and -12 are reportedly elevated [59,69,70].…”
Section: Pop In Multiple Sclerosismentioning
confidence: 98%
See 2 more Smart Citations
“…The enzymes may also release pro-inflammatory cytokines and participate in regulating the expression of the cell death signalling molecule FasL [70]. Several MMPs including MMP-2, 3 and 9 contribute to microglial toxicity [68]. In MS brain tissues MMP-2, -7, -9, and -12 are reportedly elevated [59,69,70].…”
Section: Pop In Multiple Sclerosismentioning
confidence: 98%
“…Based on this fact, Klegeris and coworkers [68] investigated microglia and their surrogate, THP-1 cells, in order to identify the proteins with potential of microglial toxicity. In these studies POP mRNA was found also to be significantly increased in both cell types.…”
Section: Pop and Glial Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent in vitro studies demonstrated that PREP contributes to the toxic effects of reactive microglial cells, as it was demonstrated that activated microglia cells expressed high levels of PREP and the supernatant of these cells demonstrated toxic effects on SH-SY5Y neuroblastoma cells. This toxic effect was reduced by selective PREP inhibitors in a dose-dependent matter (Klegeris et al, 2008). Moreover, studies in PREP-knockout mice have demonstrated the association of PREP in the processes modulating neuroplasticity through inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…This is a huge limitation for the study of CSF and human brain tissue taking into account that neurons are postmitotic cells (Bantscheff M et al, 2007). Despite this handicap SILAC is a powerful tool to study cellular pathways as polyubiquitin involment in the aetiology of AD (Dammer EB et al, 2011), neuroinflamation (McGeer EG andMcGeer PL, 2010), reactive microglia (Klegeris A et al, 2008), neurotrophin signaling (Zhang G et al, 2011), oxidative stress (Akude E et al, 2011), TDP-43 proteinopathy in frontotemporal lobar degeneration and amyotrophic lateral sclerosis (Seyfried NT et al, 2010) mitochondrial alterations in dopaminergic cells (Jin J et al, 2007) and modulation of ion channels by phosphorylation (Park KS et al, 2006). Other methods for protein quantification are multiple reaction monitoring (MRM) that has been successfully used for low abundant proteins in plasma (Anderson L and Hunter CL, 2006) and phosphopeptides quantification (Lange V et al, 2008).…”
Section: Quantitative Proteomics By Liquid Chromatography Linked To Mmentioning
confidence: 99%